1984
DOI: 10.1111/j.1432-1033.1984.tb08224.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes of glycolipids dependent on cell density of Ehrlich ascites carcinoma cells

Abstract: The glycolipid composition of Ehrlich ascites carcinoma cells was found to depend strongly on the cell density of the suspension. The general trend observed upon dilution of the cell suspension was a reduction of the less complex gangliosides GM3 and G,, with concomitant increase of the more complex gangliosides, especially GM1. The increase of the content of ganglioside GMi upon dilution was accompanied by a comparable decrease of the content of its immediate precursor, asialo-GM1, whereas the content of othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Reduction of GM3 with increasing cell density is observed in the presence of EGF. It has been reported that the cell density of a culture influences the expression of gangliosides in various cell types, including hamster kidney fibroblasts (Hakomori, 1970), mouse 3T3 fibroblasts (Yogeeswaran and Hakomori, 1975), human diploid fibroblasts at early passages (Ohsawa, 1989), mouse embryonic cells (Langenbach and Kennedy, 1978), human glioma (Liepkalns et al, 1981), mouse neuroblastoma cells (Schengrund and Repman, 1982;Kadowaki et al, 1990), and Ehrlich ascites carcinoma cells (Prokazova et al, 1984). Many of these cells exhibit ganglioside patterns characterized by increased proportions of di-and/or polysialo gangliosides with reduction of simpler ganglioside species at higher cell density.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of GM3 with increasing cell density is observed in the presence of EGF. It has been reported that the cell density of a culture influences the expression of gangliosides in various cell types, including hamster kidney fibroblasts (Hakomori, 1970), mouse 3T3 fibroblasts (Yogeeswaran and Hakomori, 1975), human diploid fibroblasts at early passages (Ohsawa, 1989), mouse embryonic cells (Langenbach and Kennedy, 1978), human glioma (Liepkalns et al, 1981), mouse neuroblastoma cells (Schengrund and Repman, 1982;Kadowaki et al, 1990), and Ehrlich ascites carcinoma cells (Prokazova et al, 1984). Many of these cells exhibit ganglioside patterns characterized by increased proportions of di-and/or polysialo gangliosides with reduction of simpler ganglioside species at higher cell density.…”
Section: Discussionmentioning
confidence: 99%